2021
DOI: 10.1007/s00391-021-01928-1
|View full text |Cite
|
Sign up to set email alerts
|

Denture-related problems of patients in acute geriatric care

Abstract: Background With increasing frailty and complaint-oriented utilization of dental care, the prevalence of oral diseases also increases. Aim To clarify whether there is a need for dental prosthodontic treatment during residential acute geriatric rehabilitation. Methods Within 3 weeks in a hospital for acute geriatric patients, 79 out of 157 newly admitted patients were interviewed as study participants (age: median 79.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These studies suggested that dental professionals should provide specialised dental interventions to inpatients that are appropriate for the patient's condition. Among the various oral environmental deteriorations observed in inpatients, 6–8 problems related to dentures have been reported to be more common in older adult patients admitted to acute care hospitals 31 . The results of the present study revealed that dental professionals need to take the lead in providing oral health management to such patients.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These studies suggested that dental professionals should provide specialised dental interventions to inpatients that are appropriate for the patient's condition. Among the various oral environmental deteriorations observed in inpatients, 6–8 problems related to dentures have been reported to be more common in older adult patients admitted to acute care hospitals 31 . The results of the present study revealed that dental professionals need to take the lead in providing oral health management to such patients.…”
Section: Discussionmentioning
confidence: 65%
“…Among the various oral environmental deteriorations observed in inpatients, [6][7][8] problems related to dentures have been reported to be more common in older adult patients admitted to acute care hospitals. 31 The results of the present study revealed that dental professionals need to take the lead in providing oral health management to such patients. Denture management is only performed by dental professionals and improves nutritional status by restoring masticatory ability.…”
Section: Ta B L Ementioning
confidence: 73%
“…OFC was classified into four resilience capacity levels [32,33]. From these parameters, the criteria with the lowest grade were used to specify the resilience capacity level (RCL) as follows [63]: RCL1: Normal. RCL2: Slightly reduced.…”
Section: Descriptive Data and Oral Functional Capacitymentioning
confidence: 99%